3D needle-punched carbon/quartz fabric reinforced nanoporous phenolic composites with co-optimized mechanics, insulation and ablation. (December 2022) - Qian, Zhen; Cai, Hongxiang; Cao, Junxiang; Wang, Peng; Li, Liang; Cao, Yu; Zhang, Yayun; Niu, Bo; Long, Donghui
Abstract: Phenolic composites are the most reliable ablatives for thermal protection system, but integrating low density, good insulation and excellent mechanical/anti-ablation performance remains challenging. Here, a density-porosity trade-off method for synthesizing mid-density and high-strength phenolic composites is proposed. This method uses 3D needle-punched preforms to reinforce nanoparticle phenolic matrix. Proper compromise between porosity and density enables phenolic matrix to combine excellent thermal insulation and acceptable mechanical properties. And in-situ micro-CT results indicate that 3D needle-punched preforms can greatly improve the mechanical performance by restricting crack propagation from felt piles to woven piles. Furthermore, the mechanical, insulative and ablative properties can be optimized using hybrid carbon/quartz preforms. The resultant composites exhibit mid-densities of ∼0.9 g/m 3 with integrated performance of high tensile strength (70–120 MPa), low thermal conductivity (0.08–0.12 W/(m·K)) and good ablation resistance. These schemes will encourage the development of phenolic composites that can withstand different heat fluxes. Graphical abstract: Image 1 Highlights: A trade-off design for mechanics/insulation of phenolic composite is proposed. The unique nanopore design for astricting gas thermal motion to achieve insulation. Real-time fracture behaviors of composites are analyzed by in-situ tensile X-ray CT. The practical insulation and anti-ablation performances are of application potency.